Eimeria SPECIES COMPOSITION AND FACTORS INFLUENCING OOCYSTS SHEDDING IN DAIRY FARM, BANDUNG, INDONESIA - Sufi, Isrok Malikus; Cahyaningsih, Umi; Sudarnika, Etih (BIOTROPIA, 2017)
Coccidiosis is one of the most widely distributed parasitic diseases of cattle throughout the world. Coccidiosis infection in ruminants was caused by Eimeria spp. Â The objective of this study was to determine Eimeria species composition and various factors influencing Eimeria oocysts shedding in dairy farm.Â This study was conducted with a cross-sectional study design in dairy farm in South Bandung District from July 2014 to January 2015. Samples were obtained from 400 dairy cattle (196 cattle at age < 6 months, 37 cattle at age 6 - 12 months and 167 cattle at age > 12 months). Fecal samples were collected, examined and counted for Eimeria species composition and numbers of oocysts per gram of feces (OPG) using McMaster technique. A questionnaire was completed for individual dairy cattle farmer to record information about cattleâ€™s health and husbandry. The effect of cattleâ€™s sex, age and type of pen flooring to OPG values were analyzed using Mann-Whitney and Kruskal-Wallis tests. The Kruskal-Wallis test was performed followed by Dunn test as a multiple comparison test. Ten species of Eimeria were identified in all infected cattle. Among the Eimeria identified species, Eimeria bovis was found to have the highest prevalence (42.5%), followed subsequently by Eimeria wyomingensis (39.1%), Eimeria bukidnonensis (32.4%), Eimeria pellita (26.3%), Eimeria auburnensis (19.6%), Eimeria zuernii (17.3%), Eimeria cylindrica (3.9%), Eimeria canadensis (3.9%), Eimeria brasiliensis (3.4%) and Eimeria alabamensis (1.1%). The numbers of oocysts shed was correlated significantly (p < 0.05) with cattleâ€™s sex and age as well type of pen flooring which influenced the infection pressure. Younger calves aged less than 6 months shed the highest amount of Eimeria oocysts than older cattle. Many factors may cause the increasing number of OPG in fecal samples. Therefore, it is important to keep good sanitation and control of Eimeria among dairy cattle in the KPBS Pangalengan dairy farm.